2019
DOI: 10.1155/2019/8023541
|View full text |Cite
|
Sign up to set email alerts
|

Potential Diagnostic and Prognostic Biomarkers of Circular RNAs for Lung Cancer in China

Abstract: Emerging evidence demonstrated that circular RNAs (circRNAs) were dysregulated in lung cancer, indicating that circRNAs might serve as novel diagnostic and prognostic biomarkers for lung cancer. However, the clinical value of circRNAs on lung cancer remains unclear. This study aimed to evaluate the efficiency of circRNAs in the diagnosis and prognosis for lung cancer in China. 2122 Chinese individuals were enrolled in this investigation for assessment of diagnostic value and examination of prognostic analysis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…It was seen apparently that the nanocomposite formed was from the prepared graphene followed by the linked GNP (Figure 2E). The fabrication of IDE surface was followed based on our established method using the silicon as the basic substrate and the aluminum electrodes were formed on the silicon as the dielectric 34,35. The fabricated IDE surface formed the clear finger and gap regions as observed under the SEM (Figure 3A).…”
Section: Resultsmentioning
confidence: 99%
“…It was seen apparently that the nanocomposite formed was from the prepared graphene followed by the linked GNP (Figure 2E). The fabrication of IDE surface was followed based on our established method using the silicon as the basic substrate and the aluminum electrodes were formed on the silicon as the dielectric 34,35. The fabricated IDE surface formed the clear finger and gap regions as observed under the SEM (Figure 3A).…”
Section: Resultsmentioning
confidence: 99%
“…Compelling evidence in the last decade indicated that circRNA play important roles in various cancer types [44–48]. In the present study, we compared the circRNA expression profiles in plasma exosomes isolated from CRC patients and healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…The detection of serum tumor markers, such as carcinoembryonic antigen (CEA), neuron-specific enolase (NSE), cytokeratin 19 fragments (CYFRA 21-1), and epidermal growth factor receptor (EGFR), are important auxiliary means for the diagnosis and evaluation of the pathological types and clinical stages of lung cancer ( 7 ). However, there are still clinical challenges in improving the patient survival rate due unsatisfied early diagnosis based on the traditional methods ( 8 , 9 ). Thus, biomarkers for early diagnosis and prognosis of lung cancer are extremely needed.…”
Section: Overview Of the Lung Cancer Screening Methodsmentioning
confidence: 99%